Formulation of Oil and Gas Production Sharing Contracts and Their Implementation in Foreign Investment in the Upstream Oil and Gas Sector: A study in the Pase Block, North Aceh - Nurdin MH, Nurdin MH; Analiansyah, Analiansyah (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
The formulation of oil and gas Production Sharing Contracts (PSCs) in Aceh differs greatly from those in other regions of Indonesia. This process shall adhere to the Government Regulation No. 23 of 2015 on the Joint Management of Oil and Gas Natural Resources in Aceh, as the legal foundation for the Aceh Government’s authority in managing these resources. Accordingly, the Aceh Government shall be involved in the drafting, amendment, and termination of the PSCs, which also includes issues related to data management, payment of signature and production bonuses, audits, transfer of participating interests, involvement of Aceh-owned enterprises, and determination of CSR funds. However, there is only one oil and gas PSC in the Pase Block, signed between the Aceh Regional Development Company and Triangle Pase Inc. on May 22, 2015. This study explored the implementation of the PSC in the context of foreign investment in the upstream oil and gas sector in Aceh. Employing a normative juridical method, the study collected data by means of interviews and literature reviews, and analyzed the data based on oil and gas regulatory frameworks. The findings revealed that the implementation of the PSC indicated several contractual obligations that were not fulfilled or were violated by Triangle Pase Inc., causing financial losses to the Aceh Regional Development Company. As a result of these violations, the Aceh Regional Development Company filed a legal claim through the Indonesian National Arbitration Board, whose decision was to reject all of the Company’s claims and to require it to pay arbitration costs. Therefore, the Aceh Regional Development Company promptly filed for the annulment of the decision issued by the Indonesian National Arbitration Board.